The measurement of costs and results in supply chain management: the case of Poland - Dobroszek, Justyna (Pomiar kosztów i wyników w zarządzaniu łańcuchem dostaw: analiza dla Polski, 2018)
Supply chain management (SCM) is a modern phenomenon in business practice and an important area of scientific discussions. In the literature it is not easy to find only one explanation of this subject because some scientists treat SCM as a separate concept, others as an expansion of the logistics function. The supply chain is a kind of modern business model that needs accurate management. To support the management process an the effective way, management accounting tools and methods may be applied. The aim of the article is to present the methods and tools of management accounting used for the measurement of costs and results in SCM. For this purpose, a survey was conducted among 40 selected enterprises in Poland. The findings indicate that on the one hand the studied organizations already use advanced management accounting tools and the methods providing information for SCM needs, on the other hand, they rarely apply them. This approach does not contribute to effective and holistic measurement of supply chain and its management
Financial Sciences. Nauki o Finansach, 2018, vol. 23, no. 3, s. 34-45
Keywords: supply chain management; management accounting; measurement; costs; logistics costs; zarządzanie łańcuchem dostaw; rachunkowość zarządcza; pomiar; koszty; koszty logistyki